Pembangunan Sistem Informasi CV Sembilan Matahari Sejahtera Berbasis Website - Timotius Nico Liaotando; Albertus Joko Santoso; Findra Kartika Sari Dewi (Jurnal Informatika Atma Jogja, 2024)
CV Sembilan Matahari Sejahtera operates in the food and beverages sector. As the number of CV customers increases. Sembilan Matahari Sejahtera, the process of recording product buying and selling transactions, checking warehouse stock, and manually managing customer data is an obstacle. Therefore, the development of a website-based information system is needed to process this data in a structured and integrated manner. The development of this website-based information system is expected to be able to solve problems at CV Nine Prosperous Suns. This system was built using Laravel as the backend framework, Vue.JS as the frontend framework and MySql as the database. The architecture used is MVC (Model, View, Controller) for the development of this system. This system has been built to overcome data processing problems on CV Nine Suns Prosper well. This system can process data in a structured and integrated manner in an information system. CV Sembilan Matahari Sejahtera bergerak di bidang food and beverages. Seiring meningkatnya jumlah pelanggan CV Sembilan Matahari Sejahtera, proses pencatatan transaksi jual beli produk, pengecekan stok gudang, dan pengelolaan data pelanggan secara manual menjadi penghambat. Oleh itu, pembangunan sistem informasi berbasis website diperlukan untuk memproses data tersebut secara terstruktur dan terintegrasi. Pembangunan sistem informasi berbasis website ini diharapkan mampu memecahkan permasalahan pada CV Sembilan Matahari Sejahtera. Sistem ini dibangun dengan menggunakan laravel sebagai framework backend, Vue.JS sebagai framework frontend dan MySql sebagai database. Arsitektur yang digunakan adalah MVC(Model, View, Controller) untuk pembangunan sistem ini. Sistem ini telah dibangun untuk mengatasi persoalan pengolahan data pada CV Sembilan Matahari Sejahtera dengan baik. Sistem ini dapat memproses data secara terstruktur dan terintegrasi dalam sebuah sistem informasi.